Solid-state additive manufacturing of porous Ti-6Al-4V by supersonic impact. (December 2020) - Moridi, Atieh; Stewart, Elizabeth J.; Wakai, Akane; Assadi, Hamid; Gartner, Frank; Guagliano, Mario; Klassen, Thomas; Dao, Ming
Highlights: 3D printing well below melting temperature can produce porous Ti alloys. Supersonic impact of powder particles is used to form solid-state bonding. Controlling powder impact velocity can produce high porosity (up to 30%). Cold sprayed porous Ti alloy can achieve higher strength than laser printed one. Post-printing heat treatment can further improve mechanical behavior. Solid-state printed porous Ti alloy is biocompatible with preosteoblast cells. Abstract: Additive manufacturing of functional metallic parts based on layer-by-layer melting and solidification suffers from the detrimental effects of high-temperature processing such as large residual stresses, poor mechanical properties, unwanted phase transformations, and part distortion. Here we utilize the kinetic energy of powder particles to form a solid-state bonding and overcome the challenges associated with the high temperature processing of metals. Specifically, we accelerated powders to supersonic impact velocities (~600 m/s) and exploited plastic deformation and softening due to high strain rate dynamic loading to 3D print Ti-6Al-4V powders at temperatures (800 °C, 900 °C) well below their melting point (1626 °C). By using processing conditions below the critical powder impact velocity and controlling the surface temperature, we created mechanically robust, porous metallic deposits with spatially controlled porosity (apparent modulus 51.7 ± 3.2 GPa, apparent compressive yield strength 535 ± 35 MPa, porosity 30 ± 2%). When the mechanical properties of solid-state 3D printed Ti-6Al-4V were compared to those fabricated by other additive manufacturing techniques, the compressive yield strength was up to 42% higher. Post heat treatment of solid-state printed porous Ti-6Al-4V modified the mechanical behavior of the deposit under compressive loading. Additionally, the 3D printed porous Ti-6Al-4V was shown to be biocompatible with MC3T3-E1 SC4 murine preosteoblast cells, indicating the potential biomedical applications of these materials. Our study demonstrates a single-step, solid-state additive manufacturing method for producing biocompatible porous metal parts with higher strength than conventional high temperature additive manufacturing techniques. Graphical abstract: Image, graphical abstract